Analysis of The Needs of Young Voters in Surakarta City on The Leadership Style of The Governor Candidate of Central Java in The 2024 Election to Realize A Strong Institution - Pangestu, Adeyasa Resi; Hellend, Arbend Ficasso Van; Dewi, Meilina Candra; Retnowati, Aminda Ayu; Lutfiasari, Dina (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
The demographic bonus in Indonesia in 2045 will have an impact on increasing the population, one of which is that the composition of the population is dominated by young people. The dominance of the young population will influence the development of a region, including the government management system. This condition is connected with the upcoming 2024 simultaneous elections, especially in Central Java, where the governor will be elected. It was recorded that 424,727 voters in the city of Surakarta were young people who were potential voters in determining regional leaders. This could also be an opportunity for gubernatorial candidates to prepare themselves to adapt the character of the leader that young people hope for. This research will specifically find out what kind of leadership style young people think can create a strong institution. 398 data collection was completed with selected respondents from the OSIS administrators and students/general. Variables (X) used as indicators of leadership style include intelligence, assertiveness, emotionality, communicativeness, experience, and trendiness. This variable will be tested for its influence on the variable (Y), namely tough institutions. The analysis of the questionnaire instrument shows valid results and very high reliability. Overall, it shows that leadership style influences the strong institutions that young people expect. This influence is shown to be 24.1%. The results of multiple linear regression analysis of the research data partially show that trend is a variable that has a high influence compared to other variables, with a t table value (5.572) > calculated r (2.2501).